Local food production in a subarctic Indigenous community: the use of willow (Salix spp.) windbreaks to increase the yield of intercropped potatoes (Solanum tuberosum) and bush beans (Phaseolus vulgaris). Issue 1 (2nd January 2018) - Barbeau, Christine D.; Wilton, Meaghan J.; Oelbermann, Maren; Karagatzides, Jim D.; Tsuji, Leonard J. S.
ABSTRACT: Addressing food security with local and sustainable food production is a key requirement for supporting a globally sustainable agricultural system. Food insecurity is prevalent in Indigenous communities in Canada, especially in rural and remote regions of northern (subarctic and arctic) Canada. Further, climate change has disproportionately impacted subarctic and arctic regions worldwide − surface air temperatures are now more favourable for agricultural activities − offering the potential for local food production under ambient conditions. The objectives of the present study were to evaluate bush bean ( Phaseolus vulgaris L.) and potato ( Solanum tuberosum L.) intercrops grown over a two-year period in two sites (treed, windbreak-lined with native willow, Salix. spp.; and non-treed, or open) in the subarctic Indigenous community of Fort Albany First Nation, Ontario, Canada. Intercrops grown in the windbreak-lined site produced significantly greater ( p < 0.05) yields and biomass than the open site. An analysis of soil chemistry (pH, P, K, Mg, NO3, NH4 and total N) showed that with some local amendments such as offal and bone meal, both the windbreak-lined and open sites can support continued agricultural use. This study informs Indigenous communities across subarctic regions of the world that climate change not only brings challenges, but also opportunities, such as potentially sustainable local food production.